Bastarnowie - źródła pisane a materiał archeologiczny - Porucznik, Joanna (Instytut Studiów Klasycznych, Śródziemnomorskich i Orientalnych Uniwersytetu Wrocławskiego, 2014)
This article aims to respond to the question of who the Bastarnae were, where they came from and what they were called. Written sources refer to the Bastarnae as Celts, Germans and sometimes even as Scythians; moreover, there also appear three variations of the name for these people: Bastarnae, Basternae and Peucini. The fundamental problem which most often recurs in research into the Bastarnae is the identification of these people with archaeological cultures.
Keywords: Bastarnae; Celts; Germans; Scythians; Danube